Pengaruh Pesan Kampanye Public Relations #FOREsponsible terhadap Citra Merek Fore Coffee : Survei Followers pada Instagram @fore.coffee - Muhamad Rizkian Fajar; Winda Dwi Astuti Zebua (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Fore Coffee's #FOREsponsible campaign prioritizes the principle of environmental conservation. They collaborate specifically with a company called Robries, which processes plastic waste into valuable products such as furniture and home decor. This study aims to determine how much influence the #FOREsponsible public relations campaign message has on Fore Coffee's brand image. The theory used is the Campaign Message theory (variable X) in accordance with Venus's research (2019), with indicators including Message Content, Message Structure, and Message Frame. Brand image (variable Y) is measured based on the dimensions of strength, favorability, and uniqueness in accordance with Keller's theory (2013). This study uses a quantitative approach with a survey method, namely by distributing questionnaires to 94 samples selected using the Slovin formula, probability sampling techniques, and simple random sampling methods. The collected data were then analyzed using simple linear regression techniques. The results of the analysis show the influence of variable X (Campaign Message) on variable Y (Brand Image). From the results of simple linear regression, the R Square value (coefficient of determination) was obtained at 63.3%, which means that approximately 63.3% of the influence on Fore Coffee's brand image comes from the #FOREsponsible campaign message on Instagram. While the remaining 37.7% is influenced by other factors not covered in this study. This proves that the campaign message has a significant influence on Fore Coffee's brand image.